Velocity-space tomography of an MeV fast-ion tail generated by three-ion scheme ICRF heating at JET - B.C.G. Reman; H. Järleblad; Y. Dong; J. Eriksson; M. Nocente; Y. Kazakov; E. Lerche; D. Van Eester; R.O. Dendy; D. Moseev; A. Snicker; M. Rud; et al. (Nuclear Fusion)
Recently-developed methods are used successfully to reconstruct the two-dimensional velocity-space distribution of the energetic minority MeV ion tail created by heating in the ion cyclotron range of frequencies (ICRFs) in the D–D $ _{NBI}$ – ^3 He three-ion scheme. This reconstruction is based on neutron emission spectroscopy and gamma-ray spectroscopy measurements of JET plasma 95679. These datasets present challenges in velocity-space tomography which are met by collisional regularisation coupled to a sparsity-promoting regularisation technique. In combination, these capture the energetic ion tail in pitch-angle as well as in energy. Our reconstructions highlight the importance of diagnostics that can probe the plasma with oblique lines-of-sight with respect to the direction of the confining magnetic field. Our inferred fast-ion distribution corroborates experimentally the pitch angle tilt of the energetic ion tail predicted analytically, and by TRANSP simulations, for the three ion ICRF scheme. The synergies between neutral-beam injection and ICRF heating are captured by these diagnostics, and we are able to validate models of electromagnetic ICRF wave heating directly from the experiments.